Distribution characteristics and pollution assessment of heavy metals in typical black soil profiles of Haicheng city, Liaoning province, China - Ziqi Li; Cang Gong; Xiaojun Ai; Xiaohuang Liu; Xiaofeng Zhao; Jiufen Liu (PLoS ONE, 2025)
In order to understand the spatial distribution, influencing factors, pollution level and sources of heavy metals in black soil profiles in Northeast China, black soil profile samples were collected from five sampling points in Haicheng City, Liaoning Province, with the deepest profile depth of 50m. The contents of heavy metals (As, Cd, Cr, Cu, Hg, Ni, Pb and Zn) in soil at different depths were analyzed, and the distribution characteristics and influencing factors of heavy metals in black soil profiles were analyzed. The pollution level of heavy metals in soil was evaluated based on the geo-accumulation index method and enrichment factor method, and the sources of heavy metals in soil were analyzed based on principal component analysis. The results show that the content ranges of As, Cd, Cr, Cu, Hg, Ni, Pb and Zn in the surface soil of the five profile sampling points are 7.74–16.5μg/g, 0.14–0.38μg/g, 75.4–104μg/g, 20.6–36.1μg/g, 0.031–0.20μg/g, 27.8–45.6μg/g, 28.5–45.6μg/g and 56.8–158μg/g, respectively. The Cd, Cr, Ni and Pb contents in the surface soil of the five profiles all exceeded the soil background values in Liaoning and China. Except for profile HCZK02, the contents of 8 heavy metals generally decrease with increasing depth. As the depth of profile HCZK02 increases, As, Hg and Pb show a decrease-increase-decrease change; Cd and Cr show a decrease change and Ni shows a zigzag change; Cu and Zn show a decreasing-increasing-decreasing-increasing trend. Corg, N, TC and TFe2O3 in the profile soil have a very significant impact on the vertical distribution characteristics of heavy metals. There are certain differences in the pollution degree of heavy metals in the surface soil of different profiles. Except for profile HCB01, where Cd and Hg in the surface soil are at moderate pollution levels, the heavy metals in the surface soil of the other profiles are at non-pollution to mild pollution levels. Principal component analysis results show that As, Cr, Cu and Ni belong to natural sources, Cd and Hg belong to anthropogenic sources from agricultural activities-atmospheric deposition, and Pb and Zn have both sources.